2013
DOI: 10.1007/s11274-013-1480-4
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant xylanase from Streptomyces coelicolor Ac-738: characterization and the effect on xylan-containing products

Abstract: A xylanase gene was isolated from the genomic DNA of Streptomyces coelicolor Ac-738. The 723-bp full-length gene encoded a 241-amino acid peptide consisting of a 49-residue putative TAT signal peptide and a glycoside hydrolase family-11 domain. The mature enzyme called XSC738 was expressed in Escherichia coli M15[pREP4]. The electrophoretically homogeneous protein with a specific activity of 167 U/mg for beechwood xylan was purified. The pH optimum of XSC738 was at pH 6; a high activity was retained within a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The DNA fragments encoding xylanases were amplified by the PCR technique with primers. PCR, cloning, expression and purification of the proteins were performed as previously described (Lisov et al 2014). Q5 DNA-polymerase (NEB) was used for the xylanases genes amplification.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The DNA fragments encoding xylanases were amplified by the PCR technique with primers. PCR, cloning, expression and purification of the proteins were performed as previously described (Lisov et al 2014). Q5 DNA-polymerase (NEB) was used for the xylanases genes amplification.…”
Section: Methodsmentioning
confidence: 99%
“…Characterization of properties of xylanases was performed as previously described (Lisov et al 2014). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A longer active life of the enzyme during hydrolysis will lead to reduced enzyme dosage, thereby making the process cost-effective. It was reported that XSC738 endo-xylanase from thermo-acidophilic S. coelicolor Ac-738 exhibited only 20% of the initial activity at 60°C for 1 h, while about 1% activity was detected for 5 min at 70°C (Lisov et al 2013), and SB-9a from Ziziphus mauritiana at 55°C only maintained 50% of its activity for 10 min (Chivero et al 2001). Temperature analyses of xylanase from S. chartreusis L1105 showed that the maximum activity of purified xynA occurred at 65°C.…”
Section: Purification Of Xyna and Truncated Derivatives And Their Chamentioning
confidence: 99%